2020
DOI: 10.1515/flin-2020-2029
|View full text |Cite
|
Sign up to set email alerts
|

Reported speech in Kakabe: Loose syntax with flexible indexicality

Abstract: Mainstream approaches to the typology of reported discourse have been based on the notion of a direct-indirect continuum: reported speech constructions are traditionally analyzed as conforming to or deviating from the “ideals” of European direct and indirect speech. This study argues that continuum-based approaches fail to distinguish between two dimensions of variation that are systematically discriminated in a number of African languages and should therefore be treated separately. First, different constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…(33) Coreference between Rel-NP and Mat-NP in Mano with mismatch in person specification [ CorC Míá lɛ ́ ō kɛ̄ yī wɛ̄] person.PL:H ATT 3PL.PST be there DEM 15 West African languages, including Mande, are known to have flexible personal indexicality in reported speech (Nikitina & Vydrina 2020), so a person mismatch alone does not constitute evidence for a break in deictic anchoring. The past tense marker, however, is a stronger indication of this.…”
Section: Person Mismatchmentioning
confidence: 99%
“…(33) Coreference between Rel-NP and Mat-NP in Mano with mismatch in person specification [ CorC Míá lɛ ́ ō kɛ̄ yī wɛ̄] person.PL:H ATT 3PL.PST be there DEM 15 West African languages, including Mande, are known to have flexible personal indexicality in reported speech (Nikitina & Vydrina 2020), so a person mismatch alone does not constitute evidence for a break in deictic anchoring. The past tense marker, however, is a stronger indication of this.…”
Section: Person Mismatchmentioning
confidence: 99%
“…We do not pay much attention to this parameter in this study, because we believe that a Eurocentric direct/indirect distinctioneither binary or gradualdoes not apply to some of our languages (Nikitina and Bugaeva 2021). We adopt instead a stratified typology, as sketched out in (Nikitina and Vydrina 2020): the construction's syntax is considered independently of the use of indexical expressions. The behavior of indexical expressions is assumed to depend on language-specific lexical properties of the words involved (pronouns, adverbs, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Alexandra's preference for a corpus-based approach to analyzing linguistic data also resulted in a study of reported speech co-authored with Tatiana Nikitina (Nikitina & Vydrina 2020). Mainstream approaches to reported speech tend to model the typological variation in reported speech structures based on a single scale, i.e.…”
mentioning
confidence: 99%